Walking in parents’ shoes? Factors behind students’ succession intentions in family firms - Suchankova, Diana; Holienka, Marian; Pšenák, Peter (European Journal of Family Business, 2023)
Succession is one of the crucial processes in family businesses, enabling them to last for generations. On one hand, more and more businesses will face a situation to choose their successors. But on the other hand, the succession intention among the young generation of potential successors has decreased. Therefore, our paper aims to fill the gap between the increasing need for new successors and their decreasing interest in taking over the family business. In doing so, we rely on GUESSS data from 2021, and our sample consists of Slovak students who consider their parents’ business as a family business (n = 575). We conclude that students’ involvement in parents’ businesses due to working experience and ownership stake significantly increases their succession intention. Further, we find out that sons want to become successors more likely than daughters. Finally and surprisingly, the birth order has no impact on succession intention. Based on these conclusions, we develop implications for further research and family business practice.